The little teashop on Main - Thomas, Jodi (HQN, 2019)
"Redheaded, curly-haired Zoe is openhearted, kind and free-spirited, and dreams of becoming a famous actor in New York City. Shy Emily struggles with mental health but has the heart and soul of a writer. And Shannon - tall, athletic, strong - has a deep sense of loyalty that will serve her well when she heads off to military college. As Zoe, Emily and Shannon grow into women - forging careers, following dreams and finding love - they'll learn that life doesn't always unfold the way they want it to, but through it all, the one constant is each other, and their regular tea parties. And when the unthinkable happens, the girls must come together to face the greatest test of all."-- Publisher description.